(untitled) (Asian Journal of Current Engineering and Maths, 2013)
An analytical study is performed to investigate the effects of chemical reaction and radiation on unsteady MHD flow past an exponentially accelerated vertical plate with variable temperature and variable mass diffusion in the presence of applied transverse magnetic field. It is assumed that the effect of viscous dissipation is negligible in the energy equation and there is a first order chemical reaction between the diffusing species and the fluid. The flow is assumed to be in xâ€™ â€ direction which is taken along the infinite vertical plate in the upward direction and yâ€™ â€ axis is taken normal to the plate. At time tâ€™ > 0, the both temperature and species concentration levels near the plate are raised linearly with time t. A general exact solution of the governing partial differential equations is obtained by usual closed analytical method. The velocity, temperature and concentration fields are studied for different physical parameters like thermal Grashof number (Gr), mass Grashof number (Gm), Schmidt number (Sc), Prandtl number (Pr), radiation parameter (R), magnetic field parameter (M), accelerated parameter (a), heat absorption parameter, chemical reaction parameter (K)Â and time (t) graphically.